Compact Stepped Impedance Resonator Bandpass Filter with Tunable Transmission Zeros - Rezki El Arif; Muhammad Aziz Muslim; Sholeh Hadi Pramono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper proposes a compact microstrip bandpass filter (BPF) with tunable transmission zeros, narrow bandwidth and low insertion loss. A λ/4 stepped impedance resonator (SIR) with two additional via holes has been adopted to obtain a compact size and a pair of transmission zero (TZ). Furthermore, three techniques have been developed to create a pair of controllable transmission zeros on both side of each passband.  The TZ can be controlled by adjusting either magnetic or electric coupling. The measured return losses and insertion loss is larger than 18 dB and 2.2 dB respectively. The overall size of the proposed design filter is 5.3mm x 5.5mm without considering the feeding lines.